Isolation and properties of endophytic bacteria and actinomycetes of Catharanthus roseus (L) G. Don grown in Nha Trang, Vietnam - Tran, My Linh; Pham, Thi Hoe; Nguyen, Chi Mai; Ninh, Khac Ban; Vu, Huong Giang; Nguyen, Tuong Van (Academia Journal of Biology, 2024)
Endophytic microbes of medicinal plants are known to involve the synthesis of several bioactive compounds, which promote plant growth and resistance to diseases. In order to investigate endophytes in the important medicinal plant Catharanthus roseus, 16 endophytic microorganism strains were isolated from root samples of C. roseus var. roseus and C. roseus var. ocellatus naturally growing in coastal areas of Nha Trang, Vietnam. Based on morphological characteristics and 16S rDNA gene marker sequences, four actinomycetes of Streptomyces and Microbiospora genera and twelve bacterial strains belonging to Bacillus, Enterobacter, Pseudomonas, Panenibacillus and Rhizobium genera were identified. Analysis of the extracellular enzyme activities of actinomycetes strains indicated that Streptomyces strains produced proteases, cellulases, xylanases and amylases and Microbiospora strains exhibited protease and cellulase activities. The results demonstrated the diversity of endophytes in the roots of C. roseus plants and their potential extracellular enzyme activities for further application.